V-034 IPOM PLUS: IS THERE ANY PLACE LEFT? WHY WE (STILL) DO IT. (13th October 2022) - Agresta, F; Licitra, E; Mazzarolo, G; Savino, G; Pontarolo, N; Montori, G
Abstract: Aim: In this video, we want to share and discuss what we have learned from our 20-year experience in IPOM PLUS, for scheduled as emergencies Material and Methods: We use only all 5 mm trocars, instruments, and 30-degree optics and we always use low intra-abdominal pressure - 10mmHg. The technical trick is to carefully prepare and manage the abdominal wall context, to free all the hernia areas. Results: Our experience is almost more than 500 cases, elective as an emergency. In the last years, we normally use a prosthesis, made with a monofilament macroporous mesh and transparent film(with the film versus the intestine), with a 5 cm overlap. Besides the well known needed physical characteristics of the mesh, on the surgeon's side, a mesh should be smooth, stiff, wide enough to cover all the possible defects, easy to handle, and, especially for its possible use in laparoscopy, with a certain degree of and thickness just what it is needed to let it pass through a 5 mm trocar once rolled up. We use to close the defect to avoid serosa and SS - Morbidity and we use to fix the mesh with absorbable tackers. Above all we do believe in the diagnostic value of the technique, cause allows us to better see and judge the intraabdominal context Conclusions: The advantages of laparoscopy rely on the minimal access and the possibility to manage and examine the abdominal context, especially in emergencies, close the defect, and fix the mesh with tackers.